Analisis Pemberian Antibiotik Berdasarkan Hasil Uji Sensitivitas Terhadap Pencapaian Clinical Outcome Pasien Infeksi Ulkus Diabetik Di RSUD DR. H. Abdul Moeloek Lampung - Kahuripan, Ardiansyah; Andrajati, Retnosari; Syafridani, Tetty (UI Scholars Hub, 2009)
The administration of antibiotic at RSUD dr. H. Abdul Moeloek Lampung is based on sensitivity test result and empirical therapy on diabetic ulcer. Therefore, the objective of the research is to analyze the effectivity of various antibiotics adminis-tration based on the sensitivity test result on clinical outcome reached by consider-ing influenced factors. On the other hand, total evaluation of the resistances of empirical antibiotic used by considering germ and sensitivity test feature was done. The research was conducted at dr. H. Abdul Moeloek Regional Hospital from April - July 2008 by applying cross sectional design retrospectively. Data was taken by the diabetic ulcer patients medical record which were treated from January 1st 2005 to Mei 30, 2009. Requirement of patient inclution are patient with diabetic ulcer infection, receiving antibiotic recipe, antibiotic given is based on sensitivity test result, patient was cured until getting the doctor approval to go home. The research which involved 98 patient inclution showed that clinical outcome of diabetic ulcer patient who was administered antibiotic based on sensitivity test result was influ-enced by chronic level of patient and age.